2002
DOI: 10.1085/jgp.20028535
|View full text |Cite
|
Sign up to set email alerts
|

Control of P2X2 Channel Permeability by the Cytosolic Domain

Abstract: ATP-gated P2X channels are the simplest of the three families of transmitter-gated ion channels. Some P2X channels display a time- and activation-dependent change in permeability as they undergo the transition from the relatively Na+-selective I1 state to the I2 state, which is also permeable to organic cations. We report that the previously reported permeability change of rat P2X2 (rP2X2) channels does not occur at mouse P2X2 (mP2X2) channels expressed in oocytes. Domain swaps, species chimeras, and point mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
91
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 40 publications
11
91
1
Order By: Relevance
“…Moreover, a chimera containing the extracellular domain of the rP2X 3 receptor flanked by the transmembrane and cytosolic domains of the rP2X 2A receptor exhibits a 30-fold lower EC 50 value compared with the rP2X 2A receptor (26). A leftward shift of the concentration-response curve is also observed when the native rP2X 2A ectodomain is substituted with the rP2X 4 ectodomain, suggesting that transmembrane domain-flanking sequences can also affect agonist potency (27).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, a chimera containing the extracellular domain of the rP2X 3 receptor flanked by the transmembrane and cytosolic domains of the rP2X 2A receptor exhibits a 30-fold lower EC 50 value compared with the rP2X 2A receptor (26). A leftward shift of the concentration-response curve is also observed when the native rP2X 2A ectodomain is substituted with the rP2X 4 ectodomain, suggesting that transmembrane domain-flanking sequences can also affect agonist potency (27).…”
Section: Discussionmentioning
confidence: 97%
“…Seven genes encoding P2X subunits (P2X [1][2][3][4][5][6][7] ) are known in mammals. All P2X subunits share a common membrane topology, with two hydrophobic membrane-spanning segments (M1 and M2) separated by a large extracellular loop of ϳ300 amino acid residues, which comprise the ATP-binding domain.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that these receptors are able to form pores but do not contain the P2X7 pore-enabling domain (residues 551-581) indicates that a separate P2X pore-forming domain may exist. Khakh and Lester (7) proposed that the change between channel and pore states was achieved through a conformational change within the selectivity filter and have recently reported that the permeation of the I 2 state of the P2X2R is modulated by specific residues (432 and 444) within the C-terminal tail (26). The truncated P2X2 a R-(1-403) was reported to be permeable to large cations (positively charged N-methyl-D-glucamine) (25), which is in contrast to the minimum length requirement of 582 residues for the P2X7R to form pores seen in the present study.…”
Section: Cell Surface Expression and Pore Formation Can Be Regulated mentioning
confidence: 99%